Influence of Proteoglycanes on Reactive Changes of Cerebral Neurons under Stress - Alexey Rozhentcev (Journal of Global Pharma Technology, 2016)
The article presents research data on the effect of proteoglycans on reactive changes in cerebellum neurocytes under the action of a stressor. We simulated hypobaric hypoxia as a stress factor affecting cerebellar neurons. This is due to the fact that hypoxic conditions are widespread and can occur both in injuries and in various diseases. The histological and histochemical methods were used to determine the effect that proteoglycans have on changes that occur in cerebellum neurocytes under the influence of a stressor. Our comprehensive studies have helped to establish that the introduction of proteoglycans in order to correct the effect of hypobaric hypoxia on cerebellum neurocytes has a positive effect on intracellular production and excretion of high molecular weight compounds. So, in the neurons of the cerebellum of rats of the experimental group, a smooth increase in the processes of physiological regeneration was noted. In addition, destructive changes in neurocytes were less pronounced compared with the control group. The ultrastructural studies of rat cerebellum nerve cells in the control group showed that under the action of hypoxia in the early stages there was an increase in the volume of intracellular structures, and then, with prolonged exposure – a decrease in their volume. This, in turn, has a negative effect on metabolic processes inside the neuron and, as a consequence, the growth of destructive changes. An experimental study showed the effectiveness of the use of proteoglycans for the correction of changes in cerebellum neurocytes under the influence of a simulated stress factor.Keywords: Hypoxia, Cerebellum, Neuron, Proteoglycans, stress factor, Ultra-structure.